Perforated diverticulitis of the sigmoid colon revealed by a perianal fistula - Amor, Imed Ben (Int J Surg Case Rep, 2015)
INTRODUCTION: Diverticular disease of the colon is a frequent pathology; however, perforated diverticulitis with a spontaneous sigmoidocutaneous fistula revealed by a perianal abscess is an uncommon presentation. We present this extremely rare case of a perforated sigmoid diverticulum in the perianal area, which is the first case that we have encountered in our practice and in the literature, along with the accompanying diagnostic and therapeutic issues and a review of the literature. PRESENTATION OF CASE: We report the case of a 47-year-old man who was admitted to the emergency room due to a perianal abscess. The patient was taken to the operating room on an emergency basis. In the lithotomy position, the abscess was located at the 4 o’clock position. Incision and drainage was performed. Intraoperatively, the abscess was found to be deep, and considered an ischiorectal abscess. No fistulous tract was identified. An MRI of the pelvis was performed one month postoperatively which revealed a perforated diverticulitis of the sigmoid colon causing a perianal fistula. After the abscess was successfully treated, a sigmoidectomy was performed. Fifteen centimeters of the colon were resected. No postoperative complications occurred. DISCUSSION: Perianal fistula is an obvious physical sign but its etiology is complex to determine. The pathophysiological mechanism involved is the emergence of a pressure gradient between the peritoneum and surrounding structures, causing rupture of the perianal tissue, allowing gas from a perforation to diffuse along tissue planes. CONCLUSION: General surgeons should bear in mind this rare presentation of a sigmoid diverticulitis.